ANALISIS PESAN MORAL DALAM FILM “ANAK NEGRI” KARYA GATOTKOCO SUROSO - Hia, Fitri Santi (Universitas Nias Raya, 2025)
This type of research is descriptive qualitative research. The data source is the conversation or storyline in the film